Adobe Photoshop elements 9 maximum performance : unleash the hidden performance of elements - Galer, Mark (Focal Press, 2011)
Let Mark Galer guide you through the most powerful photo editing tools and techniques that Elements has to offer! A unique cominbtion of step-by-step projects, movie tutorials and sample images will have you creating stunning images in no time at all. Whether you want to enhance your images for maximum impact, optimize your photos for perfect print quality, or creating impressive, seamless montages, Maximum Performance will give you the skills and know-how to create professional quality results, enabling you get maximum performance from this credit crunch approved.
Print version record
Keywords: Adobe Photoshop elements; Photography -- Digital techniques; Image processing -- Digital techniques; Photographie numérique; Traitement d'images; Techniques numériques; digital imaging; COMPUTERS; Computer Graphics; General; Image processing; Digital techniques; Photography; Digital techniques